Optimization of Triterpenoid Extracted from Vietnamese Ganoderma lucidum via Supercritical Extraction Method and Biological Tests. Issue 14 (22nd September 2022) - Dat, Tran Do; Viet, Nguyen Duc; Thanh, Vuong Hoai; Nhi, Ho Nguyen Dieu; Linh, Ngo Thi Thuy; Ngan, Nguyen Thi Kim; Nam, Hoang Minh; Thanh Phong, Mai; Hieu, Nguyen Huu
ABSTRACT: Herein, supercritical CO2 (SC–CO2 ) technique has been utilized to extract triterpenoid from Vietnamese Ganoderma lucidum ( G. lucidum ). Box–Behnken design was utilized to study the simultaneous effects between factors on triterpenoid content including extraction pressure, extraction time, and extraction temperature. Triterpenoid content was analyzed by using reversed-phase high-performance liquid chromatography with a diode array detector, using Pursuit XRs C18 reversed-phase column, the highest triterpenoid content was quantitatively analyzed for 2.735 ± 0.007 mg/g dry weight of material under optimal extraction conditions. Gas chromatography-mass spectrometry analysis revealed the presence of various compounds such as fatty acids and squalene in the ethanol extract of G. lucidum . Also, scanning electron microscopy images were used to evaluate material surfaces before and after extraction, thus proving the proposed mechanism of the extraction process by SC-CO2 . The presence of triterpenoid and its derivatives were validated by the result of Fourier transform infrared spectra. SFE-CO2 extract has strong antioxidant, antibacterial and anti-cancer properties. As a result, SC–CO2 may be considered as a viable technique for triterpenoid extraction from G. lucidum .